Students’ Needs and Motivation in ESP: Insights from Islamic-Oriented Learning Contexts - Devansa Riski Indrasara; Farikah; Umi Rachmawati (Universitas Tidar, 2025)
This study investigates the English for Specific Purposes (ESP) needs and motivation of Madrasah Aliyah students in Temanggung Regency in learning Islamic-themed English. Using a quantitative descriptive survey design, data were collected from 104 students through a 38-item Likert-scale questionnaire based on Hutchinson and Waters’ needs analysis model. The instrument demonstrated strong internal consistency (Cronbach’s Alpha = 0.89). Data were analyzed using scoring, mean calculations, categorical interpretation, and descriptive statistics. Findings show that students place high importance on Islamic English materials (M = 3.36), yet experience moderate difficulties in understanding Islamic texts and identifying main ideas (M = 2.92–2.96). Students expressed clear preferences for positive, youth-relevant Islamic content (M = 3.02–3.07) and demonstrated hybrid learning needs involving both digital media and printed textbooks (M = 3.09–3.15). Motivation increased significantly when English materials aligned with Islamic values embedded in students’ daily lives (M = 3.19–3.25). The study highlights the necessity of developing contextual Islamic-based ESP materials that support linguistic, affective, and identity-related dimensions, offering important implications for curriculum development in Islamic secondary education.